Cold start of passenger cars. (20th February 2004) - Kyriakis, N.A.; Andre, M.
Data on actual vehicle usage and operating conditions during normal driving have been collected with private cars equipped with on-board data acquisition systems. These data concern 77 vehicles, 10400 trips and 89, 000 kilometres and they are used to analyse the cold and transient operation. The paper focuses on the thermal conditions at start and during operation, in relation to usage and driving conditions. Trip lengths and parking duration are described. The engine start temperature is analysed as a function of ambient temperature and parking duration. Distances travelled and driving duration are determined for both cold and warm conditions. The corresponding traffic characteristics are compared in terms of speed and stop rates.